The Effect of Outdoor Sports and Green Outdoors on Lung Inflammation - Cecep Muhammad Alawi; Hamidie Ronald Daniel Ray; Agus Rusdiana (JUARA : Jurnal Olahraga, 2022)
This study aimed to analyze the effect of exercise in open spaces with exposure to pollution and activity in green open areas on lung inflammation. The true experimental method and The Randomized Posttest-Only Control Group Design were used in this study. Twenty-four adult male Wistar white rats weighing 200-250 grams aged 8-9 weeks were randomly divided using simple random sampling technique into four groups, NE (Non-Exercise) as control, NE+Pol (Non Exercise + Pollution Particulate Matter 2.5 >75 ppm, and Carbon Monoxide Meter <100 ppm), Ex (Exercise 5 times/week for four weeks), Ex+Pol (Exercise + pollution). The inflammatory marker Interleukin 6 (IL-6) was analyzed using Western Blotting. To determine the significant differences between groups, one-way ANOVA analysis and Post Hoc test were used. Based on the study results, it can be concluded that there is an effect of exercise in an open space with exposure to pollution on lung inflammation. And other results show that there is no effect of exercise in green open spaces on lung inflammation.